Technologies and Innovations in Regional Development: The European Union and its Strategies - Borut Rončević; Victor Cepoi (Peter Lang International Academic Publishing Group, 2022)
The subsequent volume revolves around the Social-Fields-Approach (SOFIA) as an approach to conceptualization and operationalisation for the purpose of empirical research. It contributes a new perspective and approach in research on innovation. We believe that SOFIA can have implications for both academic research and practical applications in reshaping the existing instruments and governance arrangements in innovation policy. Whilst applying SOFIA, we urge researchers to leverage the plurality of different qualitative, quantitative and mixed-method approaches in innovation studies, including less conventional methods, such as QCA (Ragin, 2008). Diligent application of SOFIA can also subsequently lead to the development of high-level theoretical contributions.
Keywords: 330; Borut; Cepoi; Development; European; Innovation; Innovations; Regional; Roncevic; Strategies; Technologies; Union; Victor; Winkelkötter